Uma análise contextual das políticas públicas voltadas para as empresas de pequeno porte no Brasil - Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Faced with the extremely heterogeneous reality of small businesses and aware of the different criteria and legal structure, existing in Brazil, to its classification and framework, this paper aims to highlight the need to establish a set of articulated objectives, the target audience and the modality of incentives to be implemented specifically for this segment segment. Therefore, the effectiveness of existing policies and the need to adopt a classification criteria consider the intrassetoriais segment heterogeneities is debated. The study clearly shows the importance of considering the centrality of these firms to national economic development, as well as to take actions aimed at increasing their productivity, considering the proactive role of the state as determinant in this process.
Keywords: N8; H25; O2; 330; small business; public policies; organizational maturity